2014
DOI: 10.1159/000355801
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Oxygen Metabolism Disorder During Septic Acute Kidney Injury

Abstract: Background/Aims: Acute kidney injury (AKI) during septic shock, which is one of the most common clinical syndromes in the intensive care unit (ICU), has a high mortality rate and poor prognosis, partly because of a poor understanding of the pathogenesis of renal dysfunction during septic shock. Although ischemic injury of the kidney has been reported to result from adenosine triphosphate (ATP) depletion, increasing evidence has demonstrated that AKI occurs in the absence of renal hypoperfusion and even occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…All surgeries were performed according to previous study [16]. Anesthesia was induced by intraperitoneal injection of pentobarbital (30 mg/kg), and continuous administration was maintained by using a mini pump (pentobarbital, 4 mg/kg/h).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All surgeries were performed according to previous study [16]. Anesthesia was induced by intraperitoneal injection of pentobarbital (30 mg/kg), and continuous administration was maintained by using a mini pump (pentobarbital, 4 mg/kg/h).…”
Section: Methodsmentioning
confidence: 99%
“…In the LPS + 3AB group, injection of 3-AB (Sigma-Aldrich, Mo., USA, 15 mg/kg [18], determined by preliminary test) was performed when the vital signs of canines were stable after operation (about 30 min), while canines in the control group accepted saline injection in the same way. In the LPS groups, input of LPS (Escherichia coli O55:B5, Sigma-Aldrich, Mo., USA) (2 mg/kg [16,19], at 1 mg/kg·min) was conducted through the pulmonary artery catheter 10 min after the administration of 3-AB or saline. Kidney samples were harvested 0, 2, 4 and 6 h after LPS injection in the LPS groups and 6 h after in control and LPS + 3AB group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to these deleterious stimuli, tubular cells dedifferentiate and release a plethora of paracrine factors as an ultimate effort to induce tissue regeneration. On the other hand, tubular cells directly contribute to systemic inflammation by carrying out immune functions, such as cytokine release and leukocyte recruitment and activation been found that during sepsis, renal oxygen consumption is significantly reduced [17]. The auto-digestion of energy-consuming organelles (autophagy), including the mitochondria (mitophagy), is one of the key passages of this biological phenomenon.…”
Section: Mechanisms Of Cellular Dysfunctionmentioning
confidence: 99%